2022
DOI: 10.3390/foods11172715
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analyses Reveal the Regulatory Mechanism of Nutrient Limitation-Induced Sporulation of Antrodia cinnamomea in Submerged Fermentation

Abstract: Antrodia cinnamomea is a precious edible and medicinal mushroom with various biological activities, such as hepatoprotection, antitumor, antivirus, immunoregulation, and intestinal flora regulation. However, the wild fruiting bodies of A. cinnamomea are scarce and expensive. Submerged fermentation based on spore inoculation has become the most efficient and popular artificial culture method for A. cinnamomea. In order to complement the mechanism of asexual sporulation of A. cinnamomea in submerged fermentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Then, the culture medium was inoculated and cultured in accordance with the method described in Section 2.2 . Samples were taken on days 6–11 to determine sporulation and biomass [ 22 ]. Medium with the same volume of deionized water added was regarded as the control group.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the culture medium was inoculated and cultured in accordance with the method described in Section 2.2 . Samples were taken on days 6–11 to determine sporulation and biomass [ 22 ]. Medium with the same volume of deionized water added was regarded as the control group.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, proteomics and transcriptome techniques were used to explore the molecular regulatory mechanism underlying the asexual sporulation of A. cinnamomea during submerged fermentation and successfully revealed the FluG-mediated asexual sporulation signaling pathway in A. cinnamomea (Li et al, 2017). In 2022, molecular regulatory mechanisms underlying the asexual sporulation of A. cinnamomea induced by nutrient restriction (Li et al, 2022a) and promoted by iron ion (Li et al, 2023) in submerged fermentation were revealed by transcriptomics. In addition, the excellent effect of A. cinnamomea polysaccharides (APSs) was observed on inflammation alleviation and intestinal flora regulation in antibiotic-induced diarrheic mice (Lu et al, 2022a(Lu et al, , 2022b.…”
Section: Introductionmentioning
confidence: 99%